Some Combinatorial Interpretations and Applications of Fuss-Catalan Numbers. (14th November 2011) - Lin Lin, Chin-Hung Chin-Hung
Abstract : Fuss-Catalan number is a family of generalized Catalan numbers. We begin by two definitions of Fuss-Catalan numbers and some basic properties. And we give some combinatorial interpretations different from original Catalan numbers. Finally we generalize the Jonah's theorem as its applications.